2015
DOI: 10.3345/kjp.2015.58.6.230
|View full text |Cite
|
Sign up to set email alerts
|

A novel association between cerebral sinovenous thrombosis and nonketotic hyperglycinemia in a neonate

Abstract: Lethargy in newborns usually indicates central nervous system dysfunction, and many conditions such as cerebrovascular events, infections, and metabolic diseases should be considered in the differential diagnosis. Nonketotic hyperglycinemia is an autosomal recessive error of glycine metabolism, characterized by myoclonic jerks, hypotonia, hiccups, apnea, and progressive lethargy that may progress to encephalopathy or even death. Cerebral sinovenous thrombosis is a rare condition with various clinical presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…An expression study of the PROC Arg147Trp variant in mammalian cell lines (HEK923) showed that the variant exhibited normal anticoagulant activity to Fva but a ∼3 times lower affinity for binding to endothelial protein C receptor (EPCR); thus the activation of this protein C variant on capillary endothelial cells could be potentially impaired and could contribute to the risk of developing venous thrombosis ( 14 ). Mutation of plasminogen activator inhibitor-1 ( PAI-1 ), another thrombosis-related gene, was previously described in a neonate with NKH and cerebral venosinus thrombosis ( 17 ). The PAI-1 variant was not found in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…An expression study of the PROC Arg147Trp variant in mammalian cell lines (HEK923) showed that the variant exhibited normal anticoagulant activity to Fva but a ∼3 times lower affinity for binding to endothelial protein C receptor (EPCR); thus the activation of this protein C variant on capillary endothelial cells could be potentially impaired and could contribute to the risk of developing venous thrombosis ( 14 ). Mutation of plasminogen activator inhibitor-1 ( PAI-1 ), another thrombosis-related gene, was previously described in a neonate with NKH and cerebral venosinus thrombosis ( 17 ). The PAI-1 variant was not found in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical series and review studies have confirmed a female predominance, with a male:female ratio of 1:3 (3,6,10,18). Female gender represents a predisposing factor for the development of CVST due to: (i) estrogen imbalance, which may be induced by oral contraceptives, pregnancy, or puerperium (10,19); (ii) a congenital hypercoagulable state, including protein C or protein S deficiency, and anti-thrombin III or V factor resistance; and (iii) a hypercoagulable state caused by other diseases, including malignant tumors, infections, nephrotic syndrome, polycythemia, leukocytosis, severe anemia, and dehydration (19)(20)(21)(22)(23). In contrast to arterial thrombosis, individuals with CVST typically present with more complicated clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Glycine encephalopathy, also known as non-ketotic hyperglycinemia (NKH) represents a disorder characterized by elevated concentrations of glycine in all body tissues, especially in plasma and cerebrospinal fluids (1)(2)(3). NKH is caused by deficiency in the glycine cleavage system (GCS).…”
Section: Introductionmentioning
confidence: 99%